The National Defense Health System And Community Understanding As A Reserve Component - Susdarwono, Endro Tri; Susnitarini, Dwi (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
This study aims to provide a description regarding public understanding as a reserve component of the national defense health system. The approach in this study uses a type of quantitative research. The research population includes all people living in Pemalang and Brebes Regencies. The sampling technique used random sampling. While the instrument used in this research is a questionnaire. The data analysis technique uses hypothesis testing through chi squared distribution. This study concludes that the proportion of respondents according to generational grouping and education level who do not understand the national defense health system is not constant so that the cause is a significant factor. Meanwhile, the proportion of respondents according to the type of work or profession who do not understand the national defense health system is constant, so the cause is purely coincidental. Based on the results of this study, it is recommended that respondents according to the grouping of generations and levels of education make structured efforts to provide an understanding of the national defense health system. So that a more in-depth understanding is obtained related to the national defense health system because the community is a reserve component that supports national defense.